2016
DOI: 10.1111/ele.12703
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in outcrossing rates and changes to floral traits are associated with the evolution of herbicide resistance in the common morning glory

Abstract: Human-mediated selection can strongly influence the evolutionary response of natural organisms within ecological timescales. But what traits allow for, or even facilitate, adaptation to the strong selection humans impose on natural systems? Using a combination of laboratory and greenhouse studies of 32 natural populations of the common agricultural weed, Ipomoea purpurea, we show that herbicide-resistant populations self-fertilise more than susceptible populations. We likewise show that anther-stigma distance,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 58 publications
(136 reference statements)
0
28
0
Order By: Relevance
“…It has been proposed that selfing may even evolve to facilitate local adaptation when there is fine grained spatial environmental heterogeneity with migration (Antonovics, ; Levin, ). Self‐fertilisation has been found to evolve in conjunction with adaptation to heavy metals (Antonovics, ; Antonovics et al ., ; Dubois et al ., ), serpentine soil (Macnair & Gardiner, ; Rajakaruna, ), and the herbicide glyphosate (Kuester et al ., ). Although our simulations did not explore if local adaptation can contribute to the evolution of selfing we showed that, even with high levels of outcrossed pollen flow, optimal trait values rapidly evolve in selfing populations over the short term (see Notes S2 for a discussion of the rate of adaptation in selfers and outcrossers).…”
Section: Discussionmentioning
confidence: 97%
“…It has been proposed that selfing may even evolve to facilitate local adaptation when there is fine grained spatial environmental heterogeneity with migration (Antonovics, ; Levin, ). Self‐fertilisation has been found to evolve in conjunction with adaptation to heavy metals (Antonovics, ; Antonovics et al ., ; Dubois et al ., ), serpentine soil (Macnair & Gardiner, ; Rajakaruna, ), and the herbicide glyphosate (Kuester et al ., ). Although our simulations did not explore if local adaptation can contribute to the evolution of selfing we showed that, even with high levels of outcrossed pollen flow, optimal trait values rapidly evolve in selfing populations over the short term (see Notes S2 for a discussion of the rate of adaptation in selfers and outcrossers).…”
Section: Discussionmentioning
confidence: 97%
“…This is likewise supported by our finding of low genome-wide patterns of linkage between SNPs, and evidence of a selective sweep, as indicated by low nucleotide diversity in this region and marks of positive selection indicating a high frequency of derived variants. Because this species employs a mixed mating system (i.e., multilocus outcrossing rate (t m ) = 0.5; [50]), it is plausible that resistance alleles, once introduced into the population, could quickly spread via outcrossing and then increase in frequency given strong selection.…”
Section: Patterns Of Haplotype Sharing Across Resistant Populations Smentioning
confidence: 99%
“…Ipomoea purpurea is a weedy annual vine that is native to the central highlands of Mexico and was introduced to the United States prior to the arrival of Columbus [4]. It is a diploid species with a genome size of 980 MB [55] and employs a mixed mating system, with some populations showing a high selfing rate and other populations exhibiting high levels of outcrossing [50]. It is consistently listed as one of the 'worst weeds of agriculture' in the Southeast and midwestern part of the United States [summarized in [4,[17][18][19][20].…”
Section: Study Speciesmentioning
confidence: 99%
“…This is a strategy that plants probably use to enhance reproductive success under conditions of stress (Levin, ) although in Vicia faba an increased rate of outcrossing was observed when plants were exposed to a simulated heat wave of 30°C for 5 days (Bishop et al ., ; for an overview of the metabolic responses of flowers to heat waves, see Box 1). Shifts in mating behavior may impact the effective size of populations, gene flow and maintenance of the genetic diversity of wild flowering species with trends which are difficult to predict in the context of natural ecosystems, as additional factors such as the evolution of herbicide resistance (Kuester et al ., ), the co‐occurrence of pollinators and herbivores in the same habitat (Moreira et al ., ) and different phenological responses to temperature (Cleland et al ., ) also influence plant reproductive success. Moreover, differential phenological responses of plant species to climate change may produce opposing consequences for population structures and consequently for species extinction.…”
Section: The Effects Of Global Warming On the Metabolism Of Flowers Omentioning
confidence: 99%